Effects of Contamination of Freshwater Habitat With Common Heavy Metals and Anions on the Prevalence of Human Adenoviruses and Enteroviruses - Wasonga, Michael Opere; Maingi, John; Omwoyo, Ombori (Frontiers in Public Health, 2021)
The occurrence and survival of enteric viruses in open surface waters can be affected by a host of factors including faecal emission levels, seasonal variations, virus stability and the physicochemical parameters. In this research, we aimed to document the association between contaminations of water samples with human enteric viruses (adenoviruses and enteroviruses) from an open environmental freshwater source with variations in chemical parameters. We collected 216 water samples from October 2010 to April 2012, from a 4 km stretch along Lake Victoria basin in Homa Bay town located in the western region of Kenya. The samples were analyzed for the presence of human adenoviruses (HAdV) and human enteroviruses (HEV), using the nested PCR (nPCR). Also studied were the water samples for contamination with twelve different chemical parameters consisting of six heavy metal elements and six anions. About 8.3 % of the samples were found to be contaminated with the enteric viruses. The concentrations of the 12 chemical parameters were found to be largely within the WHO suggested limits. The concentrations of most of them in the water samples were not correlated to the detection rates of the viral genomes based on the statistical analysis results. However, some positive and negative associations were established for three metals (Fe, Pb, and Cd) and the PO43- Radical. Cd had a weak positive significant relationship with HAdV genome detection (rho = 0.146, p = 0.032) while Pb and Fe had weak positive significant relationship with HEV genome detection (rho = 0.156, p = 0.022) and (rho = 0.148 and p = 0.029) respectively. Phosphate ion had a negative significant relationship with HEV detection (rho = -0.174, p = 0.010). The associations detected were not significant enough to infer reliability between the prevalence of viruses and the four chemical parameters.